The Effect of Work Motivation and Tenure on Post Office Employee Performance in Brebes Regency - Aris, Muhammad Adam; Syaifulloh, Muhammad; Indriyani, Azizah (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study aims to determine and analyze the effect of work motivation and tenure on employee performance. The method use in this research is quantitative descriptive analysis, which is based on facts that accur in the field. Data collection techniques using observation, interviews and questionnaires. Data analysis used in this study used the normality test, multicollinearity test and heteroscedasticity test. After going through the validity and reliability tests, then the data were analyzed using multiple linear regression tests and tests of the coefficient of determination. The researcher processed the data from the results of the questionnaire answers using the SPSS 17 application. Work in this research has an effect on employee performance. Based on the results of the coefficient of determination, an R of 0.335 or 33.5% is obtained, this indicated that variables of work motivation and length of servicehave a 33.5% influence on employee performance variables, while the remaining 66.5% is influenced by other variables not present in this study. This research was conducted at the Indonesian Post Office in Brebes Regency. The theory that supports this research and the sample used in this study is 69 respondents from 84 populations.